Residential blue space, cognitive function, and the role of air pollution in middle-aged and older adults: A cross-sectional study based on UK biobank - Kaitai Yang; Fabin Lin; Xuefei Wang; Huaicheng Wang; Yisen Shi; Lina Chen; Yanhong Weng; Xuanjie Chen; Yuqi Zeng; Yinqing Wang; Guoen Cai (Ecotoxicology and Environmental Safety)
This study examines the relationship between residential exposure to blue spaces (e.g., rivers, lakes, and seas) and cognitive function in middle-aged and older adults in the United Kingdom, with a specific focus on the mediating effects of air pollution, particularly nitrogen dioxide (NO₂) and fine particulate matter (PM2.5). Cognitive function was assessed using touch screens at UK Biobank Assessment Centre, while residential blue space exposure within a 300-meter radius was estimated from land-use data. Annual average levels of air pollution, specifically NO₂ and PM2.5, were calculated through a land-use regression model. Logistic regression models analyzed the association between blue space exposure and cognitive function, and restricted cubic splines were employed to assess potential nonlinear relationships. Causal mediation analysis quantified the indirect effects of air pollution on this relationship. The study included 35,669 participants, revealing that high blue space exposure (≥75 %) was associated with a 13.2 % lower risk of cognitive impairment compared to those with low exposure (<25 %). Notably, NO₂ and PM2.5 significantly mediated this association, with indirect effects estimated at 9.5 % and 15.85 %, respectively. These findings indicate that increased residential exposure to blue spaces is linked to a reduced risk of cognitive impairment, highlighting the protective role of blue environments in the context of air pollution. This research underscores the importance of environmentally sensitive urban planning and policies to promote public health and cognitive well-being among vulnerable populations.